Analisis Lembar Kerja Siswa Praktikum Struktur Darah berbasis Diagram Vee: (Analysis of Blood Structure Student’s Practical Worksheet based on Diagram Vee) - Yunni Handayanie; Sri Anggraeni; Bambang Supriatno (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
The Industrial Revolution 4.0 is a challenge for the quality of education in Indonesia. One way to improve the quality of education is through practical work using student’s practical worksheet. Biology Practical Worksheet on Blood Structure Subject. The study was a descriptive qualitative and the research subject was the student’s practical worksheet on blood structure. The used sampling technique was total sampling, which included six student worksheets of KTSP 2006 and four student worksheets of 2013 Curriculum. The used instruments were the instrument of conceptual analysis and practical analysis, which were self-developed, also the instrument of cognitive construction analysis based on Vee Diagram. The findings show the tested worksheet includes some issues on conceptual, procedural, and cognitive construction. The issue on conceptual relies on the work procedure which was not aligned with the objective. The issue on practical are: 1) the difficulty on object identification; 2) the recorded-data was not structured; and 3) there were no safety-lab procedure. The issue on cognitive construction are: 1) the object / event was not in accordance with focused-question; 2) the identified-concept was not based on any principle or theory; 3) the notes / transformation was not in accordance with the main procedure; and 4) the cognitive claim was not in accordance with concept, principle, or theory. Abstrak. Penelitian ini bertujuan untuk memberikan gambaran mengenai permasalahan LKS praktikum struktur darah di SMA. Penelitian ini merupakan penelitian deskriptif kualitatif dan subjek penelitian ini adalah LKS praktikum struktur darah. Teknik sampling yang digunakan yaitu total sampling, sampel terdiri dari 6 LKS pada KTSP 2006 dan 4 LKS pada Kurikulum 2013. Instrumen yang digunakan meliputi instrumen analisis konseptual dan analisis praktikal yang dikembangkan oleh penulis serta instrumen analisis kontruksi pengetahuan berdasarkan Diargam Vee. Hasil temuan menunjukkan LKS praktikum struktur darah masih terdapat masalah pada konseptual, prosedural dan konstruksi pengetahuan. Permasalahan pada konseptual yaitu langkah kerja yang tidak sesuai dengan judul/tujuan. Permasalahan pada praktikal yaitu: 1) sulitnya mengidentifikasi objek / fenomena; 2) perekaman data tidak terstruktur; dan 3) tidak adanya prosedur safety lab. Sedangkan permasalahan pada konstruksi pengetahuan yaitu: 1) objek / peristiwa tidak sesuai dengan pertanyaan fokus; 2) konsep teridentifikasi tanpa prinsip dan teori; 3) catatan / transformasi tidak sesuai dengan kegiatan utama; dan 4) klaim pengetahuan tidak sesuai dengan konsep, prinsip dan teori.